The atherogenic index of plasma (AIP) is a predictor for the severity of coronary artery disease - Li, Ya; Feng, Yujia; Li, Shu; Ma, Yulin; Lin, Jiesheng; Wan, Jing; Zhao, Min (Frontiers in Cardiovascular Medicine, 2023)
Objective: Dyslipidemia is a key risk factor for coronary artery disease (CAD). This study aimed to investigate the correlation between the atherogenic index of plasma (AIP) and the severity of CAD. Methods: 2491 patients were enrolled in this study and analyzed retrospectively, including 665 non-CAD patients as the control group and 1826 CAD patients. The CAD patients were classified into three subgroups according to tertiles of SYNTAX score (SS). Non-high-density lipoprotein cholesterol (Non-HDL-C) was defined as serum total cholesterol (TC) minus serum high-density lipoprotein cholesterol (Non-HDL-C), atherogenic index (AI) was defined as the ratio of non-HDL-C to HDL-C; AIP was defined as the logarithm of the ratio of the concentration of triglyceride (TG) to HDL-C; lipoprotein combine index (LCI) was defined as the ratio of TC∗TG∗ low-density lipoprotein cholesterol (LDL)to HDL-C; Castelli Risk Index I (CRI I) was defined as the ratio of TC to HDL-C; Castelli Risk Index II (CRI II) was defined as the ratio of LDL-C to HDL-C. Results: The levels of AIP (P<0.001), AI (P<0.001), and LCI (P = 0.013) were higher in the CAD group compared with the non-CAD group. The Spearman correlation analysis showed that AIP (r=0.075, P<0.001), AI (r=0.132, P<0.001), and LCI (r=0.072, P=0.001) were positively correlated with SS. The multivariate logistic regression model showed CRI I (OR: 1.11, 95% CI: 1.03-1.19, P = 0.005), CRI II (OR: 1.26, 95% CI: 1.15-1.39, P < 0.001), AI (OR: 1.28, 95% CI: 1.17-1.40, P < 0.001), AIP (OR: 2.06, 95% CI: 1.38-3.07, P < 0.001), and LCI (OR: 1.01, 95% CI: 1.01-1.02, P < 0.001) were independent predictors of severity of CAD After adjusting various confounders. Conclusion: CRI I, CRI II, AIP, AI, and LCI were independent predictors of the severity of CAD, which could be used as a biomarker for the evaluation of the severity of CAD. Keywords: Atherogenic index of plasma; Atherogenic index; Lipoprotein combine index; Coronary artery disease; biomarker